2021
DOI: 10.1007/s12103-020-09602-9
|View full text |Cite
|
Sign up to set email alerts
|

Hate Crimes against Asian Americans

Abstract: Using 1992-2014 data from the National Incident-Based Reporting System (NIBRS), the present study examines the nature and characteristics of hate crimes against Asian Americans by comparing them with those of hate crimes against African Americans and Hispanics. Minority-general and minority-specific models are proposed to guide the analysis. The findings are mixed. The analyses of all victim-related and most offender-related variables show similarities of hate crimes against Asian Americans to those against Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…Although Asian Americans are the fastest-growing racial group and projected to double in size to over 10% of the U.S. population by 2050, relatively few studies have examined the Asian American experience within Gen Z (Shresta & Heisler, 2011). The COVID-19 pandemic has provoked an unprecedented surge in anti-Asian racism and violence (Pew Research Center, 2021; Zhang et al, 2021). The prolonged pandemic and its devastating social and economic tolls have protracted and intensified the severity, scope, and frequency of anti-Asian discrimination (Pew Research Center, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Asian Americans are the fastest-growing racial group and projected to double in size to over 10% of the U.S. population by 2050, relatively few studies have examined the Asian American experience within Gen Z (Shresta & Heisler, 2011). The COVID-19 pandemic has provoked an unprecedented surge in anti-Asian racism and violence (Pew Research Center, 2021; Zhang et al, 2021). The prolonged pandemic and its devastating social and economic tolls have protracted and intensified the severity, scope, and frequency of anti-Asian discrimination (Pew Research Center, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The illustrative study below provides empirical data on the experiences of racial discrimination among young Asian Americans between 2014 and 2018 and how it has undermined their mental health. Even prior to the COVID-19 pandemic, racial hostility against Asian Americans was sharply on the rise (FBI, 2019; Guha, 2017; Zhang et al, 2021). Thus, we expected to see an increase in discrimination and a corresponding increase in mental distress.…”
Section: Asian American Racial Experiencementioning
confidence: 99%
“…Associating Chinese “culture” with eating bats is an example of this type of racism. Current pandemic responses reflect a long history of xenophobic blame and a climate of anti-Asian racism that has resulted in over two thousand reported hate crimes against Asian and Pacific Islander people across the United States [ 38 , 39 ]. This scapegoating has occurred in everyday acts of hatred and also in the headlines and political speeches of public figures through phrases like “the Wuhan Coronavirus” and other tropes linking contagion with people of Asian descent [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, research has shown that motivated offenders, when presented with the opportunity, are highly likely to use that opportunity to commit crimes against racial minority groups (Green et al., 2001). Notably, hate violence is found to be often perpetrated by strangers (Zhang et al., 2021) and those who are “thrill‐seekers” (Levin & McDevitt, 2013).…”
Section: Differential Vulnerabilities During the Covid‐19 Pandemicmentioning
confidence: 99%